2017
DOI: 10.14245/kjs.2017.14.3.77
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Incidence Can Be Changed not only by Age and Sex, but also by Posture Used during Imaging

Abstract: ObjectiveComputed tomography (CT), rather than conventional 2-dimensional radiography, was used to scan and measure pelvic parameters. The results were compared with measurements using X-ray.MethodsPelvic parameters were measured using both CT and X-ray in 254 patients who underwent both abdomino-pelvic CT and X-ray at the pelvic site. We assessed the similarity of the pelvic parameters between the 2 exams, as well as the correlations of pelvic parameters with sex and age.ResultsThe mean values of the subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Patients with fixed sagittal malalignment are unable to stand erect without flexing their hips or knees due to the loss of segmental lumbar lordosis (LL) 5,26,27) . Disruption of normal sagittal alignment results in significant pain and disability, and associated with low health-related quality of life 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with fixed sagittal malalignment are unable to stand erect without flexing their hips or knees due to the loss of segmental lumbar lordosis (LL) 5,26,27) . Disruption of normal sagittal alignment results in significant pain and disability, and associated with low health-related quality of life 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Higher PT and PI were reported, although not universally, in female subjects. 139 Interestingly, Mascarenhas et al 53 found higher SS and PI in asymptomatic females compared with asymptomatic males, whereas opposite observations were depicted when only considering symptomatic subjects. Some authors 143 concluded that pelvic parameters are not statistically different between sexes.…”
Section: Spinopelvic Parametersmentioning
confidence: 96%
“…With respect to age, PI and PT were found to increase with age. 134,139 Similarly, Mac-Thiong et al described a weak correlation of spinopelvic parameters with age. 144 Some studies showed no statistically significant difference.…”
Section: Spinopelvic Parametersmentioning
confidence: 98%
See 2 more Smart Citations